Seismic behaviour of steel plate shear wall with non-welded oblique multi-ribs. (June 2021) - Yu, Jinguang; Bu, Fan; Li, Bo; Feng, Xiaotian
Abstract: This paper presents a comparative study on the seismic behaviour of steel plate shear wall (SPSW) stiffened by non-welded oblique multi-ribs and reinforced concrete. Two 1/3-scale one-bay, two-storey SPSWs specimens, namely oblique multi-ribbed buckling-restrained plate (OR-BRP) and concrete buckling-restrained plate (Con-BRP), were tested under cyclic loading. The failure mode, load-carrying capacity, energy dissipation, stiffness degradation, beam-column connections rotation of SPSW structures were examined and compared. Although the stiffeners in specimen OR-BRP are more than two-thirds lighter than those in specimen Con-BRP, the results indicate that specimens OR-BRP and Con-BRP exhibit similar hysteresis behaviour in terms of stiffness degradation, energy dissipation, and load-carrying capacity. The SPSW with oblique multi ribs exhibits smaller beam-column connection deformation than that with concrete slabs. Besides, both oblique multi ribs and precast concrete slabs have similar influence on the overall deformation of columns in the SPSWs. Therefore, it is beneficial to use oblique multi-rib stiffeners in SPSW as compared with traditional concrete slabs.